Current therapies and future prospective for locally aggressive mesenchymal tumors - Maleddu, Alessandra; Zhu, Jessica; Clay, Michael Roy; Wilky, Breelyn Ann (Frontiers in Oncology, 2023)
Locally aggressive mesenchymal tumors comprise a heterogeneous group of soft tissue and bone tumors with intermediate histology, incompletely understood biology, and highly variable natural history. Despite having a limited ability to metastasize and excellent survival prognosis, locally aggressive mesenchymal tumors can be symptomatic, require prolonged and repeat treatments including toxic chemotherapies, and can severely impact patients’ quality of life. The management of locally aggressive tumors has evolved over the years with a particular focus on minimizing morbid treatments. Extensive oncologic surgeries and radiation are pillars of care for high grade sarcomas, however play a more limited role in management of locally aggressive mesenchymal tumors, due to propensity for local recurrence despite resection, and the risk of transformation to a higher grade process with radiation. Patients with these tumors should ideally be evaluated in specialized sarcoma centers to coordinate complex multimodal decision-making, taking into account the individual patient’s clinical presentation and history, as well as any available prognostic factors into customizing therapy. In this review, we aim to discuss the biology, clinical management, and future treatment frontiers for three locally aggressive mesenchymal tumors: desmoid-type fibromatosis (DT), tenosynovial giant cell tumor (TGCT) and giant cell tumor of bone (GCTB). These entities challenge clinicians with their unpredictable behavior and responses to treatment, and still lack a well-defined standard of care, despite recent progress with newly approved or promising experimental drugs.